(untitled) - Skomski, Ralph; Ralph Skomski (New York,Oxford, 2008)
This book is the first to envision the field of magnetism in its entirety. It complements a rich literature on specific models of magnetism and provides an introduction to simple models, including some simple limits of complicated models. The book is written in an easily accessible style, with a limited amount of mathematics, and covers a wide range of quantum-mechanical, finite-temperature, micromagnetic and dynamical models. It deals not only with basic magnetic quantities, such as moment, Curie temperature, anisotropy, and coercivity, but also with modern areas such as nanomagnetism and spintronics, and with 'exotic' themes, as exemplified by the polymer analogy of magnetic phase transitions
Includes bibliographical references (p. [319]-334) and index
Keywords: Magnetism